# SOLUTION: If f(x) = 2x + 1 and g(x) = (x – 1)/2 , then f(g(x)) = So, I know what to do... Basic plug and chug. I also know that the answer is X, I just don't know how to get to the answer

Algebra ->  -> SOLUTION: If f(x) = 2x + 1 and g(x) = (x – 1)/2 , then f(g(x)) = So, I know what to do... Basic plug and chug. I also know that the answer is X, I just don't know how to get to the answer      Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Mathway solves algebra homework problems with step-by-step help!

 Click here to see ALL problems on Polynomials-and-rational-expressions Question 756543: If f(x) = 2x + 1 and g(x) = (x – 1)/2 , then f(g(x)) = So, I know what to do... Basic plug and chug. I also know that the answer is X, I just don't know how to get to the answer. I plug in g(x)... f(x) = 2(x-1/2)+1, distribute... (2x-2+1)/2, combine like terms... (2x-1)/2. Now that's where I get stuck. I don't know how to get to x, unless I did my math wrong. How do I get to x?Found 2 solutions by stanbon, MathLover1:Answer by stanbon(60778)   (Show Source): You can put this solution on YOUR website!If f(x) = 2x + 1 and g(x) = (x – 1)/2 , then f(g(x)) = f[(x-1)/2] = 2[(x-1)/2]+1 = (x-1)+1 = x ================================ Cheers, Stan H. =============== Answer by MathLover1(7480)   (Show Source): You can put this solution on YOUR website!What all this says is whenever you see in then replace it with ......if then